Empowerment of The Consumer Dispute Settlement Agency (Bpsk) as Legal Protection For Consumers in Indonesia - Simanjuntak, Ade Hasiana; Harjono, Dhaniswara K.; Pieris, John; Panjaitan, Hulman; Betlehn, Andrew (International Journal of Social Service and Research, 2025)
The imbalanced position of consumers compared to business actors has led to the potential for disputes between consumers and businesses, known as consumer disputes. These disputes arise when consumers demand compensation for damages, pollution, and losses incurred from consuming goods or utilizing services. According to Law Number 8 of 1999 concerning Consumer Protection, a consumer dispute can be resolved either through the Court or out of Court. Resolving consumer disputes outside of Court is the absolute competence of the Consumer Dispute Resolution Agency. (BPSK). Normatively, the presence of BPSK provides many benefits to consumers; however, in practice, this is not the case, and in many instances, it often fails to provide legal protection to consumers. This includes issues related to the distribution of BPSK, which is not easily accessible to consumers as it is not available in all districts/cities. There are several contradictory regulations in its management, including human resource constraints, that, in many ways, need an understanding of the legal aspects of dispute resolution, especially regarding its position as a quasi-judicial body. Therefore, as a form of legal protection for consumers, BPSK must be empowered in various aspects.